Genetic characterization of caffeine degradation by bacteria and its potential applications - Summers, Ryan M.; Mohanty, Sujit K.; Gopishetty, Sridhar; Subramanian, Mani (Microbial biotechnology, 2015)
Summary The ability of bacteria to grow on caffeine as sole carbon and nitrogen source has been known for over 40 years. Extensive research into this subject has revealed two distinct pathways, N‐demethylation and C‐8 oxidation, for bacterial caffeine degradation. However, the enzymological and genetic basis for bacterial caffeine degradation has only recently been discovered. This review article discusses the recent discoveries of the genes responsible for both N‐demethylation and C‐8 oxidation. All of the genes for the N‐demethylation pathway, encoding enzymes in the Rieske oxygenase family, reside on 13.2‐kb genomic DNA fragment found in Pseudomonas putida CBB5. A nearly identical DNA fragment, with homologous genes in similar orientation, is found in Pseudomonas sp. CES. Similarly, genes for C‐8 oxidation of caffeine have been located on a 25.2‐kb genomic DNA fragment of Pseudomonas sp. CBB1. The C‐8 oxidation genes encode enzymes similar to those found in the uric acid metabolic pathway of Klebsiella pneumoniae. Various biotechnological applications of these genes responsible for bacterial caffeine degradation, including bio‐decaffeination, remediation of caffeine‐contaminated environments, production of chemical and fuels and development of diagnostic tests have also been demonstrated. This review article discusses the recent discoveries of the genes responsible for bacterial caffeine degradation via two distinct pathways, N‐demethylation and C‐8 oxidation. All of the genes for the N‐demethylation pathway reside on 13.2‐kb genomic DNA fragment found in Pseudomonas putida CBB5 and a nearly identical DNA fragment, with homologous genes in similar orientation, is found in Pseudomonas sp. CES. Similarly, genes for C‐8 oxidation of caffeine have been located on a 25.2‐kb genomic DNA fragment of Pseudomonas sp. CBB1. Various biotechnological applications of these genes responsible for bacterial caffeine degradation, including bio‐decaffeination, remediation of caffeine‐contaminated environments, production of chemical and fuels, and development of diagnostic tests have also been demonstrated.